The triacylglycerol structure of coconut oil determined by chromatography combined with stereospecific analysis - Pham, Laura J.; Gregorio, Myla A. (2008)
The study aimed to establish the acylglycerol profile, triacylglycerol molecular species and the fatty acid distribution in the three positions of the glycerol moiety of coconut (Cocos nucifera L.) oil for its biomodification into high value products to make it competitive and flexible. Analytical tools used were thin layer chromatography (TLC) for the separation of the acylglycerol classes, gas liquid chromatography (GC), high pressure liquid chromatography (HPLC) and a combination of HPLC-GC to determine the triacylglycerol (TAG) molecular species in terms of carbon number (CN) and equivalent carbon number (ECN). Stereospecific analysis, which is the distribution of the fatty acids in the glycerol backbone, was carried out using pancreatic lipase (E.C.3.1.1.3) and phospholipase A2 (E.C.3.1.1.4). The major TAG species was the fraction ECN 36 containing CN 36-42 acyl carbons. Stereoanalyses showed that lauric (C12) acid was the major fatty acid in the three positions of the glycerol moiety. Saturated fatty acids showed a general preference for the external positions, while the unsaturated fatty acids oleic and linoleic occurred predominantly at the sn-2 positions. Lauric (C12) followed by myristic (C14) and palmitic (C12) acids were preferentially esterified at the sn-1 position. Highest percentage of the medium chain fatty acids capryllic (C8), capric (C10) and lauric (C12) were found in the sn-3 position. The data established on the triacylglycerol composition and stereospecificity of coconut oil as well as the analytical methods on the determinations would be very helpful in facilitating evaluation of products from its biomodification.
Keywords: Coconut oil